PCR-Based Detection of VIM Carbapenemase Genes in Clinical Pseudomonas aeruginosa Isolates from Libyan Hospitals - Sara Rahouma (Khalij-Libya Journal of Dental and Medical Research, 2026)
Pseudomonas aeruginosa (P. aeruginosa) is the commonest human pathogen recognized for its ubiquity, its intrinsically advanced antibiotic resistance mechanisms, and its association with serious illnesses, especially hospital-acquired infections. An interest has centered on the emer-gence of strains with VIM (Verona integron-encoded metallo-β-lactamase). As there is little in-formation on the detection of such genes in P. aeruginosa from patients of the Middle East and Arab countries, including Libya, such information needs to be further investigated. However, the occurrence of VIM genes among P. aerogenousa clinical isolates in Libyan hospitals was investigated in this study. To achieve this goal, a total of 106 P. aeruginosa isolates had been collected from the stocks of the well-known teaching hospital in Tripoli, namely the Burn and Plastic Surgery Center (BPSC), for a period of 12 months between 2016 and 2017. Isolated organisms were identified to the species level and tested for their susceptibility to a variety of antimicrobial agents. The MBL-producing P. aeruginosa isolates were screened for the blaVIM gene using PCR-based methods. The results of the antibiotic susceptibility testing revealed that all isolates except for colistin were found to be resistant to the tested antibiotics to varying degrees. The VIM-positive isolates among MDR isolates were 10.7%, and among XDR isolates was 1.3%. The VIM-positive isolates (20%) had significantly higher rates of resistance to cer-tain antibiotics compared to VIM-negative isolates (80%). The high rate of antibiotic resistance among P. aeruginosa strains expressing the blaVIM gene is alarming and can be responsible for serious infections, especially among hospitalized patients; therefore, appropriate infection control measures and guidelines need to be established to reduce these infections among pa-tients.